Wartime governance and state-building trajectories in post-conflict societies - Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
To date, there is limited understanding about the consequences of wartime dynamics for post-war state-building processes. This paper explores one such dynamics-the forms of governance exercised by armed groups during wartime-and proposes a theoretical framework outlining how forms of wartime governance affect trajectories of state-building in the aftermath of civil wars. Six possible trajectories are mapped out: stable democracy, weak democracy, stable autocracy, fragmented rule, contested autocracy, and durable disorder. Each trajectory is shaped by the interaction between two dimensions of wartime governance: how armed groups build institutional capacity in wartime and the characteristics of wartime civilian rule by armed groups. The core argument is that civil wars generate within themselves bureaucratic and institutional capacity-through how armed groups govern territories and civilians within them-that under certain circumstances may be harnessed in the post-war period to build states capable of governing. The characteristics and durability of those forms of wartime governance shape the type of statebuilding and political regime trajectories that emerge in the post-war period.
Keywords: 330; political violence; war; conflict; state-building; peace; development